International Joint Conference : 12th International Conference on Computational Intelligence in Security for Information Systems (CISIS 2019) and 10th International Conference on EUropean Transnational Education (ICEUTE 2019) : Seville, Spain, May 13th-15th, 2019 : proceedings /: 12th International Conference on Computational Intelligence in Security for Information Systems (CISIS 2019) and 10th International Conference on EUropean Transnational Education (ICEUTE 2019) : Seville, Spain, May 13th-15th, 2019 : proceedings. ([2019]) - Unknown
No abstract available